Well-Tempered Women : Nineteenth-Century Temperance Rhetoric - Mattingly, Carol, 1945- (Book collections on Project MUSE., 1998)
"In this Illustrated Study, Carol Mattingly examines the rhetoric of the temperance movement, the largest political movement of women in the nineteenth century." "Tapping previously unexplored sources, Mattingly uncovers new voices and different perspectives, thus greatly expanding our knowledge of temperance women in particular and of nineteenth-century women and women's rhetoric in general. Her scope is broad: she looks at temperance fiction, newspaper accounts of meetings and speeches, autobiographical and biographical accounts, and minutes of national and state temperance meetings." "Examining the choices these women made in their efforts to better conditions for women, Mattingly looks first at oral rhetoric among nineteenth-century temperance women. She examines the early temperance speeches of activists like Susan B. Anthony and Elizabeth Cady Stanton, who later chose to concentrate their effort in the suffrage organizations, and those who continued to work on behalf of women primarily through the temperance topic, such as Amelia Bloomer and Clarina Howard Nichols. Finally, she examines the rhetoric of members of the Woman's Christian Temperance Union - the largest organization of women in the nineteenth century."--Jacket.